2002
DOI: 10.1074/jbc.m200966200
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Molecular Characterization of Nucleobase Transport by Recombinant Human and Rat Equilibrative Nucleoside Transporters 1 and 2

Abstract: The human (h) and rat (r) equilibrative (Na ؉ -independent) nucleoside transporters (ENTs) hENT1, rENT1, hENT2, and rENT2 belong to a family of integral membrane proteins with 11 transmembrane domains (TMs) and are distinguished functionally by differences in sensitivity to inhibition by nitrobenzylthioinosine and coronary vasoactive drugs. Structurally, the proteins have a large glycosylated loop between TMs 1 and 2 and a large cytoplasmic loop between TMs 6 and 7. In the present study, hENT1, rENT1, hENT2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
152
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 54 publications
5
152
0
6
Order By: Relevance
“…The importance of this region is further supported by our mutagenesis data, which identified that key residues for substrate recognition are located in TM5. Our data are consistent with results from chimeric studies of the ENTs, which also showed that the N-terminal half (TM1-6) of ENT1 and -2 contains critical domains for substrate/inhibitor recognition (21,22). Together, these results indicate that despite the distinct substrate selectivity and low sequence homology, PMATs and the ENTs share a similar protein modular organization.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The importance of this region is further supported by our mutagenesis data, which identified that key residues for substrate recognition are located in TM5. Our data are consistent with results from chimeric studies of the ENTs, which also showed that the N-terminal half (TM1-6) of ENT1 and -2 contains critical domains for substrate/inhibitor recognition (21,22). Together, these results indicate that despite the distinct substrate selectivity and low sequence homology, PMATs and the ENTs share a similar protein modular organization.…”
Section: Discussionsupporting
confidence: 81%
“…Based on these data, we hypothesized that despite the difference in substrate selectivity, PMAT and ENTs may share a similar tertiary structure and a similar arrangement of functional domains for substrate recognition and translocation. Earlier studies have suggested that the N-terminal half (TM1-6) of ENT1 and ENT2 contains critical domains for substrate/inhibitor recognition and translocation (21,22). To test our hypothesis, we first constructed two chimeric transporters, chimeras T1-6 and T7-11, between human PMAT and the prototype human equilibrative nucleoside transporter, hENT1 (Fig.…”
Section: Function and Substrate Selectivity Of Pmat And Hent1mentioning
confidence: 99%
“…hENT1 and hENT2 mediate the well-characterized equilibrative-sensitive (es) and equilibrative-insensitive (ei) processes. Although both hENT1 and hENT2 have similar selectivities for nucleosides, hENT2 also recognizes and transports hypoxanthine and other purine nucleobases (Osses et al, 1996;Baldwin et al, 1999;Yao et al, 2002). The role of hENT3 and hENT4 in nucleoside transport processes has not yet been established (Baldwin et al, 2003).…”
Section: Functional Characterizationmentioning
confidence: 99%
“…Studies of the properties of chimeras between human and rat ENTs have established that transmembrane domains 3-6 contain residues responsible for sensitivity or resistance to coronary vasodilators (Sundaram et al, 1998) and to NBMPR (Sundaram et al, 2001b). Transmembrane domains 1-6 of ENT2 appear to be responsible for transport of 3 0 -deoxynucleosides (Yao et al, 2001) while transmembrane domains 5-6 appear to be involved in its transport of nucleobases (Yao et al, 2002). Using site-directed mutagenesis, binding of NBMPR to recombinant hENT1 produced in Saccharomyces cerevisiae has been investigated.…”
Section: Structure-activity Studiesmentioning
confidence: 99%
“…CNT1 and CNT2 both transport uridine and adenosine, but are otherwise selective for pyrimidine (hCNT1 and rCNT1) and purine (hCNT2 and rCNT2) nucleosides (Huang et al, 1994;Che et al, 1995, Yao et al, 1996aWang et al, 1997;Ritzel et al, 1997Ritzel et al, , 1998. hCNT3, its mouse (m) orthologue mCNT3 and a close relative from Eptatretus stouti, an ancient marine prevertebrate, transport both pyrimidine and purine nucleosides (Ritzel et al, 2001;Yao et al, 2002b). The relationships of these proteins to transport processes defined by functional studies are: ENT1 (es), ENT2 (ei ), CNT1 (cit), CNT2 (cif ) and CNT3 (cib).…”
Section: Introductionmentioning
confidence: 99%